CRYOAPPLICAION IN ASEPTIC NECROSIS OF THE FEMORAL HEAD IN AN EXPERIMENT - Слизовский, Григорий Владимирович; Кужеливский, Иван Иванович; Шикунова, Яна Владимировна; Ситко, Леонид Александрович; Сигарева, Юлия Андреевна (Mother and Baby in Kuzbass, 2018)
The study included 24 rabbits of both sexes. After experimental detection of the optimal cryoregenerative refrigerant exposure, animals underwent a number of surgical interventions against asynthetic necrosis of the femoral head due to tunneling and cryoexposure to the focus of osteonecrosis for optimizing osteoreparative processes of bone tissue in the animals of the group, the group basis and tunneling without cryoexposure in animals of the comparison group. The control group consisted of 8 animals, which did not undergo surgical interventions.According to the data of histomorphological studies, we detected an actively developing neo-osteogenesis, which indicates the effectiveness of the 3-second exposure procedure for optimizing osteohystogenesis under the experimental model of aseptic necrosis of the femoral head.The obtained results of experimental studies make it possible to apply the proposed developed method of cryoapplication to pathologically altered bone tissue in the treatment of Legg-Calve-Perthes disease in a necrotically altered head.
Keywords: titanium nickelide; kryoregeneration; osteochondropathy; the disease Legge-Calve-Perthes